Acid‐sensing ion channels regulate nucleus pulposus cell inflammation and pyroptosis via the NLRP3 inflammasome in intervertebral disc degeneration. (27th October 2020) - Zhao, Kangcheng; An, Ran; Xiang, Qian; Li, Gaocai; Wang, Kun; Song, Yu; Liao, Zhiwei; Li, Shuai; Hua, Wenbin; Feng, Xiaobo; Wu, Xinghuo; Zhang, Yukun; et al.
Abstract: Objective: Lactate accumulation is an important factor in the intervertebral disc degeneration (IVDD). Currently, the effect and underlying mechanism of action of lactate on nucleus pulposus (NP) cell inflammation during IVDD are unclear. Previous studies have found that the NLRP3 inflammasome plays an important role in the regulation of NP inflammation. This study focused on the regulation of acid‐sensitive ion channels (ASICs) in relation to inflammation and the effect of NLRP3 on pyroptosis levels in NP cells under acidic conditions. Design: For the in vitro experiments, human NP cells were exposed to 6 mM lactate solution; different groups were either treated with NLRP3 inhibitor or transfected with siRNA against NLRP3, siRNA against ASC or a mix of these, and mRNA and protein expression levels were then assessed. For the in vivo experiment, varying concentrations of lactate were injected into rat intervertebral discs and examined via magnetic resonance imaging (MRI) and histological staining. Results: Extracellular lactate promoted NLRP3 inflammasome activation and degeneration of the NP extracellular matrix; furthermore, it increased the levels of inflammation and pyroptosis in the NP. Lactate‐induced NLRP3 inflammasome activation was blocked by ASIC inhibitors and NLRP3 siRNA. Conclusions: Extracellular lactate regulates levels of intercellular reactive oxygen species (ROS) through ASIC1 and ASIC3. ROS activate the NF‐κB signalling pathway, thus promoting NLRP3 inflammasome activation and IL‐1β release, both of which promote NP degeneration. Abstract : Schematic Illustration of NLRP3 Inflammasome Activation and Pyroptosis in Lactate‐stimulated Human NP Cells. Extracellular lactate induces Ca 2+ influx by stimulating ASIC1a and ASIC3 on the cell membrane. As a second messenger, Ca 2+ promotes an increase in intracellular ROS. ROS increases NLRP3 inflammasome component expression through the NF‐κB signaling pathway. NLRP3 components assemble and activate in the cells, leading to IL‐1β release and pyroptosis.